PENERAPAN STANDAR AKUNTANSI KEUANGAN ENTITAS MIKRO, KECIL DAN MENENGAH (EMKM) PADA USAHA DAGANG TOKO RIZKY BUSANA Tahun 2019 - Iswandir Iswandir (JURNAL MITRA MANAJEMEN, 2021)
ABSTRACTWith the existence of SAK EMKM, classic problems such as access to capital facilities from financial institutions have begun to be resolved because the regulation stipulates the expansion of funding and facilitation of banks and non-bank financial service institutions. Banks began to aggressively distribute loans to EMKM. Toko Rizky Busana in its development makes very simple notes because it does not consider financial reports important, reports that are made are only a recap of the amount of cash, accounts receivable, payable and inventory that is calculated at the end of Ramadan. So far, Rizky Busana Shop has not implemented Financial Accounting Standards for Micro, Small and Medium Entities in the recording and preparation of Financial Statements. By recording in accordance with SAK EMKM, it is hoped that in the future the company can access the facilities provided by the government. Keywords: SAK EMKM, Financial Accounting Standards, Financial Statements